Identification and pathogenicity test of Curvularia species causing fruit rot disease on pomelo (Citrus maxima) - Salim, Siti Fairuz (2016)
Pomelo (Citrus Maxima) is a citrus tree belongs to the family Rutaceae native to Southeast Asia and Indochina. Pomelo fruit contains high nutritional value including vitamin A, C and B, minerals dietary fiber and many phytochemical which make it as one of the most consumed fruit worldwide. In Malaysia, the production of pomelo is estimated to be 8830 metric tonnes in 2009 and about 1895 ha of pomelo are grown commercially. In Malaysia, there is limited research on the composition of fungal species responsible for fruit rot disease on pomelo. Fruit rots symptoms are not acceptable for sale as fresh fruit and can reduce the market value of the crop. The objectives of this study are; 1) to isolate pure culture of fungal isolates causing fruit rot on pomelo; 2) to identify fungal pathogens to species level based on morphological characteristics and polymerase chain reaction (PCR) protocol using ITS4 and ITS5 primers; and 3) to construct a phylogenetic tree using ITS analysis. To accomplish these objectives, symptomatic fruits was collected from harvested pomelo fruits at Kampung Gapis, Nyalas Melaka. Infected tissues (5 x 5 mm) from the lesion margins was surface disinfected for 2 min with 10% chlorox and sterile water and transferred on potato dextrose agar (PDA). The internal transcribed spacer (ITS) region of the ribosomal DNA was amplified using primers ITS4 and ITS5. The PCR products of the ITS were sequenced and analyzed using BLAST nucleotide search in GenBank. Pathogenicity test was conducted on six asymtomatic pomelo fruits. Both wounded and unwounded pomelo fruit were sprayed with a runoff fungal spore suspension (1 x 106) spores/ml prepared from 27-day-old cultures grown on PDA. Controls were treated with distilled water. The plastic bags were used to cover inoculated pomelo fruits to maintain high humidity. Mycelial growth and development of fruit spot symptoms were observed and Curvularia lunata was isolated from diseased fruit. This study will add information causing fruit rot on pomelo in Peninsular Malaysia and therefore, effective management of this disease must involve control of this pathogen.